Colorectal Cancer Complicating Crohn's Disease - Hugh J Freeman (Canadian Journal of Gastroenterology)
Some earlier studies have indicated that patients with inflammatory bowel disease, especially those with long-standing and extensive ulcerative colitis, have an increased risk of colorectal cancer. Moreover, others in tertiary care centres have suggested that patients with Crohn's disease also have a higher risk of colorectal cancer. Canadian data on colorectal cancer in Crohn's disease appear to be limited. For this investigation, a single clinician database of 877 patients with Crohn's disease was used. Altogether, there were six patients with colorectal cancer (ie, overall rate of 0.7%). All of these patients were men with an initial diagnosis of Crohn's disease established at a mean age of approximately 28 years, with either ileocolonic disease or colonic disease alone, but not with ileal disease alone. Although there was a predominance of women in the overall study population (ie, 56.1%), no women developed colorectal cancer. The clinical behaviour of Crohn's disease was classified as nonstricturing in all six patients with colorectal cancer, but in two patients, Crohn's disease was complicated by a perirectal abscess or a fistula. All cancers were located in the rectum and were diagnosed 30 years, 22 years, seven years, 18 years, 20 years and 40 years after Crohn's disease was initially diagnosed. In three patients, the cancer was detected in a residual rectal stump after a partial colon resection at least 10 years earlier. In five patients, localized extension of disease through the serosa, nodal or distant metastases (ie, liver, lung) was found at the time of cancer diagnosis; two patients have since died. The present study confirms that Crohn's disease involving the colon may be a possible risk factor for the development of colorectal cancer, at least in younger men, but, in this study, not in women. However, part of this increased risk in men may have been related to the presence of a rectal stump, rather than to Crohn's disease per se.